The Phase II Urokinase-Streptokinase Pulmonary Embolism Trial - Sasahara, Arthur A; Bell, William R; Simon, Toby L; Stengle, James M; Sherry, Sol (Thrombosis and Haemostasis, 1975)
The controlled clinical trials of thrombolytic agents in the United States have been carried out in two phases, under the auspices of the National Heart and Lung Institute. Phase I was devoted to the comparison of 12-hour Urokinase (12h–UK) followed by heparin (H) with heparin alone in patients with acute pulmonary embolism (Walsh et al. 1969). The results showed that patients treated with UK had more rapid and greater resolution of pulmonary thromboemboli in the first twenty-four hours of therapy than patients treated with H alone, as assessed by serial pulmonary angiography, hemodynamics and lung scanning (The Urokinase Pulmonary Embolism Trial, 1970, 1973 ; Hyers et al. 1970). Because of the relatively small size of the Trial and the low mortality of treated pulmonary embolism, mortality differences were not sought - nor was one found. Although there was early difference in amount of clot resolution, patients treated with H alone showed similar improvement by two weeks.The Phase II Urokinase-Streptokinase Pulmonary Embolism Trial (USPET) was begun to assess the comparative results of UK and Streptokinase (SK) therapy. Because of favorable results obtained with SK in other countries, it was deemed necessary to make this comparison (Browse and James, 1964 ; Hirsh et al. 1968 ; Miller et al. 1969, 1971 ; Chesterman et al. 1969). A third group, 12-hour UK, was added to relate this study (24-hour UK and SK) with the Phase I results which employed only a 12-hour infusion of UK. This Phase II Trial represents the first controlled, randomized study of UK and SK in thromboembolic disorders.